A cobalt-free oxygen electrode material regulated by b-site high valence elements and a preparation method and application thereof
Patent Information
- Application Number
- CN202611101161.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-13
AI Technical Summary
首先,钴基材料的热膨胀系数通常较大,易与电解质材料产生热膨胀不匹配,在高温烧结、热循环或长期运行过程中可能引起电极/电解质界面开裂、剥离,进而导致电池性能衰减甚至失效
[0016]本发明的氧电极材料为ABO3型单钙钛矿结构,通过在B位引入高价态过渡金属元素进行掺杂调控,可有效增强材料的晶体结构稳定性,抑制高温运行过程中结构退化,提高材料的长期稳定性。同时,B位高价态过渡金属元素的掺杂还有利于降低材料的热膨胀系数,改善氧电极与电解质之间的热匹配性,从而减少电池在高温烧结、热循环及长期运行过程中因热应力积累而引起的界面开裂、剥离及性能衰减。
Smart Images

Figure CN122907659A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid oxide battery technology, specifically relating to a cobalt-free oxygen electrode material regulated by high-valence elements at the B site, its preparation method, and its application. Background Technology
[0002] Energy is a crucial material foundation for ensuring national economic development and social progress. Solid oxide batteries (SOCs) are a class of highly efficient energy conversion and storage devices, possessing advantages such as an all-solid-state structure, high energy conversion efficiency, and wide fuel adaptability, showing promising application prospects in fields such as high-efficiency power generation and electrolytic conversion. SOCs typically consist of a fuel electrode, a dense electrolyte layer, and an oxygen electrode. Among these, the oxygen electrode is where oxygen reduction and oxygen evolution reactions occur, and its catalytic activity and operational stability significantly impact battery performance. Therefore, developing highly active and stable oxygen electrode materials is an important research area in the field of SOCs.
[0003] Currently, the oxygen electrode materials commonly used in SOCs are mostly cobalt-based perovskite oxides, such as La. 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ (LSCF), Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF), etc. These materials typically possess good electronic conductivity and oxygen electrocatalytic activity, but several problems remain in practical applications. First, cobalt-based materials generally have a high coefficient of thermal expansion, easily leading to thermal expansion mismatch with electrolyte materials. This can cause cracking and delamination at the electrode / electrolyte interface during high-temperature sintering, thermal cycling, or long-term operation, resulting in battery performance degradation or even failure. Second, some cobalt-based materials also suffer from insufficient structural stability, weak CO2 resistance, and decreased long-term stability under high-temperature operating conditions. Furthermore, the relatively high price of cobalt hinders the large-scale application of SOCs. Therefore, developing a cobalt-free oxygen electrode material that combines good thermal matching, high structural stability, and excellent electrochemical performance is of great significance for promoting the development of solid oxide batteries. Summary of the Invention
[0004] The purpose of this invention is to provide a cobalt-free oxygen electrode material regulated by high-valence elements at the B site, its preparation method, and its application. By introducing high-valence transition metal elements at the B site for doping regulation, the thermal expansion coefficient of the oxygen electrode material is reduced, and its thermal matching with the electrolyte is improved, thereby reducing interface cracking, peeling, and performance degradation caused by thermal stress during battery preparation and operation.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0006] A cobalt-free oxygen electrode material with B-site high-valence element regulation, wherein the oxygen electrode material has an ABO3 type mono-perovskite structure and the general formula is: Ba 1-x A x Fe 1-y B y O 3-δ Wherein, A is a lanthanide element or an alkaline earth metal, the lanthanide element including La, Pr, Sm or Gd, and the alkaline earth metal including Ca; B is a high-valence transition metal element, the high-valence transition metal element including Zr, Nb, Mo, Ta or W; x and y satisfy 0≤x, y≤1, δ is the oxygen nonstoichiometric coefficient, and 0≤δ≤1.
[0007] Preferably, the oxygen electrode material is Ba. 0.95 La 0.05 FeO 3-δ Ba 0.95 La 0.05 Fe 0.95 Zr 0.05 O 3-δ BaFe 0.9 Nb 0.1 O 3-δ BaFe 0.8 Nb 0.2 O 3-δ Or BaFe 0.7 Nb 0.3 O 3-δ .
[0008] This invention also provides a method for preparing a cobalt-free oxygen electrode material regulated by a high-valence element at the B site, comprising the following steps:
[0009] (1): According to the stoichiometric ratio of each element in the oxygen electrode material, weigh the metal nitrates or oxides corresponding to Ba, A, Fe and B as initial raw materials, add the initial raw materials to deionized water and dissolve them under heating conditions of 80-120 °C, and then add ethylenediaminetetraacetic acid and citric acid monohydrate as complexing agents to obtain a mixed solution.
[0010] (2): The pH of the resulting mixed solution was adjusted to 7-8 using ammonia water, and then heated and stirred continuously at 80-120 °C to gradually evaporate the water and obtain a viscous black gel.
[0011] (3): The black gel was calcined at 250-300 °C for 5-10 h to obtain the precursor;
[0012] (4): The obtained precursor was calcined at 1000-1200 °C for 5-10 h to obtain oxygen electrode material.
[0013] Preferably, in step two, the molar ratio of metal ions, ethylenediaminetetraacetic acid and citric acid monohydrate is 1:1:(1.5-2.0).
[0014] The present invention also provides an application of a cobalt-free oxygen electrode material in a solid oxide battery, the solid oxide battery including an oxygen ion-conducting solid oxide battery and a proton-conducting solid oxide battery.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0016] The oxygen electrode material of this invention has an ABO3-type single perovskite structure. By introducing high-valence transition metal elements at the B-site for doping, the crystal structure stability of the material can be effectively enhanced, structural degradation during high-temperature operation can be suppressed, and the long-term stability of the material can be improved. Simultaneously, the doping of high-valence transition metal elements at the B-site also helps to reduce the coefficient of thermal expansion of the material and improve the thermal matching between the oxygen electrode and the electrolyte, thereby reducing interface cracking, delamination, and performance degradation caused by thermal stress accumulation during high-temperature sintering, thermal cycling, and long-term operation of the battery.
[0017] The oxygen electrode material of this invention has excellent CO2 resistance and can maintain good structural and chemical stability in CO2-containing environments or complex operating conditions. This effectively reduces the risk of surface side reactions and performance degradation that are common in traditional oxygen electrode materials, and improves the reliability and durability of the material in practical applications. Attached Figure Description
[0018] Figure 1 Ba in Example 1 0.95 La 0.05 FeO 3-δ (BLF) powder and Ba 0.95 La 0.05 Fe 0.95 Zr 0.05 O 3-δ XRD pattern of (BLFZ) powder at room temperature;
[0019] Figure 2 The XRD patterns of chemical compatibility of BLFZ powder mixed with BZCYYb1711 (a) and GDC (b) in Example 1 are shown.
[0020] Figure 3 The thermal expansion coefficient curves of BLF powder and BLFZ powder in Example 1 are shown.
[0021] Figure 4For the BLF powder and BLFZ powder in Example 1, at 650 o C. XRD pattern after treatment under 1% CO2 atmosphere for 10 h;
[0022] Figure 5 The H2O temperature-programmed desorption spectra of BLF powder and BLFZ powder in Example 1 are shown.
[0023] Figure 6 The impedance spectrum of the symmetric cell assembled from BLFZ powder in Example 1, with GDC and BZCYYb1711 as electrolytes, is shown in Figure 1 (a: 800 μm using GDC as electrolyte). o C and 750 o Impedance spectrum under C, b: 700 with GDC as electrolyte o C and 600 o Impedance spectrum under C, c: with BZCYYb1711 as electrolyte 700 o Impedance spectrum under C, d: 650 with BZCYYb1711 as electrolyte. o C and 600 o Impedance spectrum under C);
[0024] Figure 7 The performance diagrams in Example 1 are shown when BLFZ powder is used as the oxygen electrode of an oxygen ion-conducting solid oxide battery (a) and a proton-conducting solid oxide battery (b) in fuel cell mode.
[0025] Figure 8 The image shows the long-term stability of BLFZ powder in Example 1 when it is used as the oxygen electrode in both oxygen ion-conducting and proton-conducting solid oxide batteries, in fuel cell mode.
[0026] Figure 9 BaFe in Example 2 0.9 Nb 0.1 O 3-δ (BFN91), BaFe 0.8 Nb 0.2 O 3-δ (BFN82) and BaFe 0.7 Nb 0.3 O 3-δ XRD pattern of (BFN73) powder at room temperature;
[0027] Figure 10 The image shows the chemical compatibility XRD pattern of the mixture of BFN82 powder and BZCYYb1711 in Example 2.
[0028] Figure 11The thermal expansion coefficient curves of BFN91, BFN82 and BFN73 powders in Example 2;
[0029] Figure 12 For example, the BFN91 powder and BFN82 powder in Example 2 were subjected to a temperature of 600°C. o C. Conductivity stability diagrams under different CO2 concentration atmospheres;
[0030] Figure 13 The impedance spectrum of the symmetrical battery assembled from BFN82 powder using BZCYYb1711 as the electrolyte in Example 2 is shown in Figure 2 (a: at 650°C). o C and 600 o Impedance spectrum at C, b: at 550 o C and 500 o Impedance spectrum under C);
[0031] Figure 14 The graphs show the performance of BFN82 powder as the oxygen electrode in a proton-conducting solid oxide battery in Example 2, under fuel cell mode (a) and electrolysis mode (b). Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described below with reference to embodiments. It should be noted that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention; that is, the described embodiments are merely some embodiments of the invention, and not all embodiments.
[0033] Example 1
[0034] This embodiment provides a cobalt-free oxide electrode material Ba. 0.95 La 0.05 Fe 0.95 Zr 0.05 O 3-δ The preparation method and steps are as follows:
[0035] (1): According to the chemical formula Ba 0.95 La 0.05 Fe 0.95 Zr 0.05 O 3-δ The stoichiometric ratio of the elements in the solution is 0.95:0.05:0.95:0.05. Weigh out 2.483 g of barium nitrate, 0.217 g of lanthanum nitrate hexahydrate, 3.838 g of ferric nitrate nonahydrate, and 0.215 g of zirconium nitrate pentahydrate, and place them in a beaker. Add 100 mL of deionized water to the beaker and place it at 100°C. oThe mixture was continuously stirred on the heating plate until all the metal nitrates were completely dissolved, resulting in a clear and homogeneous metal salt solution. Then, 6.336 g of citric acid monohydrate was added to the solution, and after it was completely dissolved, 5.874 g of ethylenediaminetetraacetic acid (EDTA) was added as a complexing agent. The mixture was stirred continuously to obtain a homogeneous mixed solution.
[0036] (2): The pH of the mixed solution obtained in step (1) was adjusted to 7 using ammonia, and the system was kept heated and stirred on the heating plate. As the water gradually evaporated, the mixed solution gradually turned into a black gel.
[0037] (3): Place the black gel obtained in step (2) in a 300°C container. o The precursor powder was calcined in a high-temperature oven at C for 10 h to obtain a fluffy precursor powder.
[0038] (4): Place the precursor powder obtained in step (3) in a muffle furnace and heat it at 1100 °C. o The target oxygen electrode material Ba can be obtained by calcining at C for 5 h and then naturally cooling. 0.95 La 0.05 Fe 0.95 Zr 0.05 O 3-δ , denoted as BLFZ.
[0039] Comparative Example 1
[0040] Ba was prepared using the same method as in Example 1. 0.95 La 0.05 FeO 3-δ (BLF) powder was used as a control sample.
[0041] Figure 1 XRD patterns of BLF and BLF2 powders at room temperature. Figure 1 It can be seen that both BLF and BLFZ powders have good crystallinity and a single perovskite structure, and no obvious impurity phases were observed. This indicates that the target material can be successfully prepared by the above method, and that a small amount of Zr doping does not destroy the main crystal structure of the BLFZ material.
[0042] The chemical compatibility of BLFZ with different electrolyte materials was tested.
[0043] The electrolyte material is BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (BZCYYb1711) or gadolinium-doped cerium oxide (GDC), weigh 0.1 g of BLFZ powder and mix it with equal masses of BZCYYb1711 and GDC powder respectively. After ball milling for 1 h, the mixture is then subjected to a 1000-fold grinding process. oCalcination at C for 5 h, followed by XRD testing, yielded the following results: Figure 2 As shown. By Figure 2 It can be seen that no new impurity phase peaks appeared after the mixed samples were calcined, indicating that BLFZ has good chemical compatibility with proton conductor electrolyte BZCYYb1711 and oxygen ion conductor electrolyte GDC, and is suitable as an oxygen electrode material for the corresponding battery system.
[0044] Test the thermal expansion behavior of BLFZ.
[0045] Weigh 2 g of BLF and 2 g of BLFZ powder respectively, add them to 5 mL of anhydrous ethanol, and add 0.04 g of polyvinyl butyral as a binder. Ball mill until the slurry is completely dry. Pass the resulting dried powder through a 200-mesh sieve and place it into a 3 mm × 4 mm × 10 mm rectangular strip mold. Press under 200 MPa for 5 min to obtain a rectangular sample strip; then press at 1250... o Calcination at C for 5 h yielded a dense sample strip. The obtained sample strip was placed in a thermal dilatometer to test its temperature from room temperature to 1000 °C. o The coefficient of thermal expansion in the range of C is as follows: Figure 3 As shown.
[0046] Test results show that the coefficient of thermal expansion of BLF is 25.11 × 10⁻⁶. -6 K -1 The coefficient of thermal expansion of BLFZ is 22.47 × 10⁻⁶. -6 K -1 This indicates that introducing high-valence Zr elements at the B site can effectively reduce the coefficient of thermal expansion of the material, which is beneficial to improving its thermal matching with components such as the electrolyte, thereby enhancing the stability of the battery during operation.
[0047] CO2 resistance test of BLFZ.
[0048] To evaluate the structural stability of the two materials in a CO2 atmosphere, BLF and BLFZ powders were placed at 650 °C. o C. Treat the sample in an air atmosphere containing 1% CO2 for 10 h, then test its XRD pattern. The results are as follows: Figure 4 As shown. By Figure 4 It can be seen that BLF produced a significant BaCO3 impurity phase after treatment, while BLFZ maintained good structural stability under the same conditions, and no obvious impurity phase formation was observed. This result indicates that incorporating high-valence Zr elements at the B site can effectively improve the structural stability of the material and enhance its resistance to CO2.
[0049] Figure 5 The results of H2O temperature-programmed desorption of BLF and BLF2 materials are presented. Figure 5 It is evident that BLFZ exhibits superior water adsorption capacity, indicating that Zr doping helps enhance the material's ability to adsorb and activate water, thereby facilitating the hydration process and further promoting proton conductivity. This suggests that BLFZ is not only suitable for oxygen-ion-conducting solid oxide battery systems but also has application potential in proton-conducting solid oxide battery systems.
[0050] Furthermore, using BZCYYb1711 and GDC as electrolytes, respectively, a BLFZ oxygen electrode symmetric cell was constructed. Its polarization impedance was measured in an air atmosphere containing 3 vol% H2O and a dry air atmosphere at a gas flow rate of 50 mL / min. The results are as follows: Figure 6 As shown in the figure. The test results show that the BLFZ composite oxygen electrode exhibits low polarization resistance in both types of electrolyte systems, indicating that the material has good oxygen electrode reactivity and fast electrode reaction kinetics.
[0051] BLFZ was applied as an oxygen electrode material in both oxygen-ion-conducting and proton-conducting solid oxide batteries, and its electrochemical performance in fuel cell mode was tested. The results are as follows: Figure 7 As shown. By Figure 7 It can be seen that in oxygen-ion conductive solid oxide batteries using SSZ / GDC as the electrolyte, at 800 o The highest power density obtained under C is 877 mW / cm². 2 In a proton-conducting solid oxide battery using BZCYYb1711 as the electrolyte, at 700... o The highest power density achievable at C is 968 mW / cm². 2 BLFZ exhibits excellent output performance in both battery systems, indicating that the material is suitable for both oxygen ion conductor and proton conductor systems and has obvious bifunctional oxygen electrode characteristics.
[0052] At a constant current density of 0.5 A / cm 2 Under the conditions described above, long-term stability tests were conducted on the two types of single cells, and the results are as follows: Figure 8 As shown. By Figure 8 It can be seen that both types of batteries maintained good stability during continuous operation for more than 200 hours without significant performance degradation, further demonstrating that BLFZ has excellent structural stability and electrochemical operational stability under actual working conditions.
[0053] In summary, the Ba prepared in this embodiment... 0.95 La 0.05 Fe 0.95 Zr 0.05 O3-δ (BLFZ) material not only has good phase formation properties, excellent chemical compatibility with a variety of electrolytes, low coefficient of thermal expansion and strong resistance to CO2, but also exhibits good water adsorption capacity, low electrode polarization impedance and excellent single cell performance and long-term stability. This indicates that the material is a high-performance cobalt-free oxygen electrode material with potential for both oxygen ion conduction and proton conduction applications.
[0054] Example 2
[0055] This embodiment provides a cobalt-free oxide electrode material BaFe. 0.8 Nb 0.2 O 3-δ Unlike Example 1, which focuses on constructing a bifunctional oxygen electrode material compatible with both oxygen ion conductors and proton conductors, this example primarily targets proton-conducting solid oxide battery systems, using BaFeO... 3-δ By introducing pentavalent Nb elements into the B site of the base material, the structural stability, thermal expansion behavior, and CO2 resistance of the material are controlled to obtain a cobalt-free oxygen electrode material that has both excellent oxygen electrode activity and reversible operation capability.
[0056] The specific preparation steps are as follows:
[0057] (1): According to the chemical formula BaFe 0.8 Nb 0.2 O 3-δ The stoichiometric ratio of the elements in the solution is 1:0.8:0.2. Weigh out 2.614 g of barium nitrate, 3.232 g of ferric nitrate nonahydrate, and 0.607 g of ammonium oxalate hydrate, and place them in a beaker. Add 100 mL of deionized water and place the beaker at 100°C. o The mixture was continuously stirred on the heating plate until all the metal salts were completely dissolved, resulting in a clear and homogeneous metal salt solution. Then, 6.336 g of citric acid monohydrate was added to the solution, and after it was completely dissolved, 5.874 g of ethylenediaminetetraacetic acid (EDTA) was added as a complexing agent. The mixture was stirred continuously to obtain a homogeneous mixed solution.
[0058] (2): The pH of the mixed solution obtained in step (1) was adjusted to 7 using ammonia, and the system was kept heated and stirred on the heating plate. As the water evaporated, the mixed solution gradually turned into a black gel.
[0059] (3): Place the black gel obtained in step (2) in a 300°C container. o The precursor powder was calcined in a high-temperature oven at C for 10 h to obtain a fluffy precursor powder.
[0060] (4): Place the precursor powder obtained in step (3) in a muffle furnace and heat it at 1100 °C. oThe target oxygen electrode material BaFe can be obtained by calcining at C for 5 h and then naturally cooling. 0.8 Nb 0.2 O 3-δ (BFN82).
[0061] Comparative Example 2
[0062] BaFe was prepared using the same method as described above. 0.9 Nb 0.1 O 3-δ (BFN91) and BaFe 0.7 Nb 0.3 O 3-δ (BFN73) powder was used as a control sample to investigate the effect of different Nb doping contents on material properties.
[0063] Figure 9 XRD patterns of BFN91, BFN82, and BFN73 powders at room temperature. Figure 9 It can be seen that all three powders exhibit good crystallinity and form a single perovskite structure, with no obvious impurity phase peaks observed, indicating that the above method can successfully prepare the target material. Furthermore, with the increase of Nb doping at the B site, the main crystal structure of the material remains stable, indicating that the appropriate introduction of high-valence Nb elements does not damage BaFeO. 3-δ The perovskite framework of the base material.
[0064] Testing the chemical compatibility between BFN82 and the proton-conducting electrolyte.
[0065] Weigh 0.1 g of BFN82 powder and mix it with an equal mass of BZCYYb1711 powder. After ball milling for 1 h, the mixture is then subjected to a 1000 mL precipitate. o Calcination at C for 5 h, followed by XRD testing, yielded the following results: Figure 10 As shown. By Figure 10 It can be seen that no new impurity phase peaks appeared after the mixed sample was treated at high temperature, indicating that BFN82 and the proton conductor electrolyte BZCYYb1711 have good chemical compatibility and can meet the application requirements of BFN82 as the oxygen electrode material of proton-conducting solid oxide batteries.
[0066] Test the thermal expansion behavior of BFN82.
[0067] 2 g of BFN91, 2 g of BFN82, and 2 g of BFN73 powder were weighed and added to 5 mL of anhydrous ethanol. 0.04 g of polyvinyl butyral was added as a binder, and the mixture was ball-milled until the slurry was completely dry. The resulting dried powder was passed through a 200-mesh sieve and then placed into a 3 mm × 4 mm × 10 mm rectangular molding die. The die was pressed at 200 MPa for 5 min to obtain a rectangular sample strip. Subsequently, it was subjected to a 1250°C test.o Calcination at C for 5 h yielded a dense sample strip. The obtained sample strip was placed in a thermal expansion apparatus to test its temperature change from room temperature to 800°C. o The coefficient of thermal expansion in the range of C is as follows: Figure 11 As shown.
[0068] Test results show that the coefficient of thermal expansion of BFN91 is 22.48 × 10⁻⁶. -6 K -1 The coefficient of thermal expansion of BFN82 is 20.42 × 10⁻⁶. -6 K -1 The coefficient of thermal expansion of BFN73 is further reduced to 18.16 × 10⁻⁶. -6 K -1 This indicates that introducing pentavalent Nb at the B site can effectively reduce the coefficient of thermal expansion of the material, thereby improving the thermal matching between the oxygen electrode material and the electrolyte, and contributing to the improvement of the structural stability of the battery during operation.
[0069] CO2 resistance test of BFN91.
[0070] To further evaluate the electrochemical stability of the materials under a CO2 atmosphere, dense sample strips obtained from the sintering of BFN91 and BFN82 powders were placed at 600°C. o C. The conductivity changes in air atmospheres with different CO2 concentrations were measured using the DC four-probe method, and the results are as follows: Figure 12 As shown. By Figure 12 It can be seen that, compared with BFN91, BFN82 exhibits superior stability and less conductivity decay under different CO2 atmospheres, indicating that appropriate Nb doping can effectively improve the structural and electrochemical stability of the material in CO2-containing environments, enhancing its resistance to CO2. This suggests that the introduction of pentavalent Nb at the B site not only optimizes the crystal structure but also helps improve the stability of the material under complex working atmospheres.
[0071] Furthermore, a BFN82 oxygen electrode symmetric cell was constructed using BZCYYb1711 as the electrolyte, and its polarization impedance was tested in an air atmosphere containing 3 vol% H2O at a gas flow rate of 50 mL / min. The results are as follows: Figure 13 As shown in the figure. The test results show that the BFN82 oxygen electrode exhibits low polarization resistance in the proton-conducting electrolyte system, indicating that the material has high oxygen electrode reactivity and fast electrode reaction kinetics under medium and low temperature conditions, making it suitable as a high-performance oxygen electrode material for proton-conducting solid oxide batteries.
[0072] Subsequently, BFN82 was applied to a proton-conducting solid oxide battery as an oxygen electrode material, and its electrochemical performance in fuel cell mode and electrolysis mode was tested. The results are as follows: Figure 14 As shown. By Figure 14 It can be seen that in the power generation mode at 650 o C yields 844.19 mW / cm² 2 The highest power density; in water electrolysis mode, at 650 o -1.62 A / cm² can be obtained under C and 5% water vapor conditions. 2 With a high electrolysis current density, BFN82 exhibits excellent output performance in both operating modes, indicating that the material not only has good fuel cell performance but also high electrochemical performance under electrolysis conditions, demonstrating excellent reversible operation performance.
[0073] In summary, the BaFe prepared in this embodiment... 0.8 Nb 0.2 O 3-δ (BFN82) material exhibits good phase formation properties, excellent chemical compatibility with proton-conducting electrolytes, low coefficient of thermal expansion, and stronger resistance to CO2. It also demonstrates low polarization resistance and excellent reversible operation performance in proton-conducting solid oxide battery systems, indicating that this material is a high-performance cobalt-free electrode material suitable for reversible proton-conducting solid oxide batteries.
[0074] This invention enhances the crystal structure stability of Fe-based mono-perovskite oxygen electrode materials by introducing high-valence transition metal elements at the B-site for doping, thereby improving the material's resistance to CO2 and reducing its coefficient of thermal expansion. This improves the thermal matching between the oxygen electrode material and the electrolyte, mitigating performance degradation caused by interfacial thermal stress accumulation during high-temperature fabrication and long-term operation. Furthermore, the oxygen electrode material possesses electron, oxygen ion, and proton conductivity, making it a triple-conductive oxygen electrode material suitable for both oxygen ion-conducting and proton-conducting solid oxide batteries.
[0075] This invention provides a cobalt-free oxygen electrode material, which avoids the problems of high cost, large coefficient of thermal expansion and insufficient long-term stability caused by cobalt in traditional cobalt-based oxygen electrode materials. Therefore, the oxygen electrode material has the advantages of low raw material cost, flexible composition design and broad application prospects.
[0076] The oxygen electrode material of this invention possesses electron, oxygen ion, and proton conduction capabilities simultaneously, making it a high-performance triple-conducting oxygen electrode material. Therefore, it can be used not only in oxygen ion conduction solid oxide batteries but also in proton conduction solid oxide batteries, exhibiting excellent multifunctional characteristics and a wider range of applications.
[0077] The oxygen electrode material of the present invention can be applied to oxygen ion-conducting solid oxide batteries and proton-conducting solid oxide batteries.
[0078] In an oxygen-ion conductive solid oxide battery, the battery consists of a dense electrolyte layer, a porous fuel electrode, and a porous oxygen electrode; the oxygen electrode is BLFZ; the electrolyte is one of 8 mol% yttrium-stabilized zirconium oxide (8YSZ), 10 mol% scandium oxide and 1 mol% cerium oxide co-stabilized zirconium oxide (SSZ), or gadolinium-doped cerium oxide (GDC); the fuel electrode consists of NiO, electrolyte, and pore-forming agent, wherein the pore-forming agent is one of polymethyl methacrylate, graphite, or starch, NiO accounts for 50-60% of the total mass of NiO and electrolyte, and the pore-forming agent accounts for 5-20% of the total mass of NiO and electrolyte.
[0079] In a proton-conducting solid oxide battery, the battery consists of a dense electrolyte layer, a porous fuel electrode, and a porous oxygen electrode; the oxygen electrode is BLFZ; and the electrolyte is BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (BZCYYb1711), BaZr 0.4 Ce 0.4 Y 0.1 Yb 0.1 O 3-δ (BZCYYb4411) or BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ One of (BZCY172); the fuel electrode is composed of NiO, electrolyte and pore-forming agent, wherein the pore-forming agent is one of polymethyl methacrylate, graphite or starch, NiO accounts for 50-60% of the total mass of NiO and electrolyte, and the pore-forming agent accounts for 5-20% of the total mass of NiO and electrolyte.
[0080] The above are merely preferred embodiments of the present invention and do not constitute any limitation on the present invention. Any equivalent substitutions or modifications made by those skilled in the art to the technical solutions and content disclosed in the present invention without departing from the scope of the present invention shall be deemed to have remained within the protection scope of the present invention.
Claims
1. A cobalt-free oxygen electrode material regulated by a high-valence element at the B site, characterized in that, The oxygen electrode material is an ABO3 type single perovskite structure with the general formula: Ba 1-x A x Fe 1-y B y O 3-δ Wherein, A is a lanthanide element or an alkaline earth metal, the lanthanide element including La, Pr, Sm or Gd, and the alkaline earth metal including Ca; B is a high-valence transition metal element, the high-valence transition metal element including Zr, Nb, Mo, Ta or W; x and y satisfy 0≤x, y≤1, δ is the oxygen nonstoichiometric coefficient, and 0≤δ≤1.
2. The cobalt-free oxygen electrode material with B-site high-valence element regulation according to claim 1, characterized in that, The oxygen electrode material is Ba 0.95 La 0.05 FeO 3-δ , Ba 0.95 La 0.05 Fe 0.95 Zr 0.05 O 3-δ , BaFe 0.9 Nb 0.1 O 3-δ , BaFe 0.8 Nb 0.2 O 3-δ or BaFe 0.7 Nb 0.3 O 3-δ .
3. A method for preparing a cobalt-free oxygen electrode material with B-site high-valence element regulation as described in claim 1 or 2, characterized in that, Includes the following steps: (1): According to the stoichiometric ratio of each element in the oxygen electrode material, weigh the metal nitrates or oxides corresponding to Ba, A, Fe and B as initial raw materials, add the initial raw materials to deionized water and dissolve them under heating conditions of 80-120 °C, and then add ethylenediaminetetraacetic acid and citric acid monohydrate as complexing agents to obtain a mixed solution. (2): The pH of the resulting mixed solution was adjusted to 7-8 using ammonia water, and then heated and stirred continuously at 80-120 °C to gradually evaporate the water and obtain a viscous black gel. (3): The black gel was calcined at 250-300 °C for 5-10 h to obtain the precursor; (4): The obtained precursor was calcined at 1000-1200 °C for 5-10 h to obtain oxygen electrode material.
4. The preparation method according to claim 3, characterized in that, In step two, the molar ratio of metal ions, ethylenediaminetetraacetic acid and citric acid monohydrate is 1:1:(1.5-2.0).
5. The application of a cobalt-free oxygen electrode material as described in claim 1 or 2 in a solid oxide battery, characterized in that, The solid oxide battery includes oxygen ion conduction type solid oxide battery and proton conduction type solid oxide battery.